Validity of the effective injection barrier in organic field-effect transistors. (24th December 2020) - Lee, Yongjeong; Horowitz, Gilles; Jung, Sungyeop; Bonnassieux, Yvan
Abstract: The injection barrier is a key parameter that governs the charge and current density in organic field-effect transistors (OFETs). However, the energetic disorder of organic disordered semiconductors (ODSs) hinders a clear definition of the injection barrier. We study the validity of effective injection barrier at the metal/organic disordered semiconductor by means of systematic numerical simulation of OFETs in full consideration of the Gaussian density-of-states. The contact resistance from the numerical simulation and analytical model are compared to verify this procedure. By varying the Gaussian width, the effective injection barrier is validated for low degree of disorder at which the semiconductor is under non-degenerate condition. The position of Fermi level with respect to the Gaussian width distinguishes the non-degenerate and degenerate condition of ODSs, indicating clearly the range of validity of the effective injection barrier.